LIBRARY RESOURCES, SERVICES AND USE AS FACTORS INFLUENCING PUBLICATION OUTPUT OF FISHERIES SCIENTISTS IN NIGERIA (2013)
Fisheries research support libraries in Nigeria are at the centre of information provision for fisheries research and development. As part of their responsibilities, they are expected to contribute to the increased publication output of the fisheries scientists which seems to be low. Available studies focused on the effect of library resources and services on publication output of agricultural scientists in general while there is a dearth of studies on the influence of factors that could affect the publication output of fisheries scientists in particular. This study, therefore, investigated library resources, services and use as factors influencing publication output of fisheries scientists in Nigeria. The Survey research design of the ex- post facto type was adopted. The Multi-stage random sampling procedure was used to select 335 fisheries scientists and 24 librarians (n = 359) from the three fisheries research institutes, three colleges of fisheries, 18 departments of fisheries in federal and state universities in Nigeria and 24 heads of the libraries. Six instruments were used for data collection: Fisheries Scientists' Questionnaire on Library Use (r = 0.71); Publication Output Questionnaire (r =0.77); Librarians' Questionnaire on Availability of Library Resources (r = 0.73); Availability of Library Services (r = 0.68); Use of Library Resources (r = 0.81) and Use of Library Services (r = 0.76). Six research questions were answered and five hypotheses tested at 0.05 level of significance. Data were subjected to descriptive statistics, Pearson Product Moment Correlation and Multiple Regression. The following proportions of the respondents indicated that computer based and other library resources and services were available, functional and adequate in their libraries: CD-ROM (40.9%); Internet (60.3%); print resources (83.6%); library staff (90.4%); reference services (79.2%) loans (66.7%) photocopying services (54.2%) and Selective Dissemination of Information (SDI) (37.5%). Majority of the participants (62.7%) found journals most useful. There was a significant joint influence of availability of library resources, availability of library services, adequacy of library services, use of library resources and use of library services (R = 0.26) on publication output of the fisheries scientists (F(5,329) 5.83, P < .05). This implies that 6.7% of the variance in the publication output was accounted for by the combination of the independent variables in the dependent variable. The relative significance of four of the independent variables was: availability of library resources (? = -.140, t = 2.55, P< 0.05); availability of library services (? = 0.156, t = 2.68, P<0.05) use of library resources (? = -.147, t = 2.13, P<0.05) and use of library services (? -.141, t=2.18, P<0.05). This implies that adequacy of library services, unlike these other variables, did not have remarkable influence on the publication output of fisheries scientists in Nigeria. Library resources, services and use jointly, relatively highly contributed to the publication output of fisheries scientists in Nigeria. Fisheries research libraries need to increase provision of CD-ROM, Selective Dissemination of Information and other information resources and services for increased publication output of fisheries scientists in Nigeria.